Searching for lost worlds Atlantis : mystery of the Minoans - Armstrong, Jane.; Rowley, Christopher; Tsikalas, John.; French, Stuart; Kiley, Richard; Lint, David; Discovery Channel (Firm).; CineNova Production ([Bethesda, Md.] CineNova, 2007)
This mini-series profiles one of the greatest discoveries of the 20th century, that in the early 1900s, an archaeologist is said to have uncovered a splendid lost civilization at Knossos called the Minoans, who have similarities with the civilization of Plato's Atlantis.
Distributed in the Philippines through MagnaVision, Quezon City.
Executive producer, David Lint ; executive producer for the Discovery Channel, Angus Yates ; series editors, Jane Armstrong and Stuart Samuels.
John Tsikalas and Stuart French (actors) ; narrated by Richard Kiley.
Keywords: Evans, Arthur -- Sir -- 1851-1941.; Marinatos, Spyridon -- 1901-1974.; Atlantis (Legendary place); Minoans; Civilization, Mycenaean; Excavations (Archaeology) -- Greece -- Thera Island; Knossos (Extinct city) -- Antiquities; Crete (Greece) -- Antiquities